Model Pembelajaran PjBL Berbasis Tringo Berbantuan Media VR untuk Meningkatkan Kemampuan Berfikir Kritis, Pemecahan Masalah Pada Pembelajar - Fitri, Karina Rahmah; Hehakaya, Enjelli; Rukmi , Jayanti Noor Purbo; Kuswandi , Dedi; Wedi , Agus (Innovative: Journal Of Social Science Research, 2025)
This research investigates the implementation of the Project-Based Learning (PJBL) model based on the Tringo strategy supported by Virtual Reality (VR) technology to enhance critical thinking and problem-solving skills in students. Amid the rapid development of educational technologies, VR offers a more immersive and interactive learning experience, increasing student engagement in the learning process and enriching their understanding of the concepts being taught. The Tringo strategy, which focuses on developing 21st-century skills such as digital literacy, critical thinking, and problem-solving, is combined with PJBL to create a collaborative, project-based, and solution-oriented learning environment. This study employs an experimental research method with a pre-test post-test design involving two student groups. The experimental group applied the PJBL model based on Tringo and VR, while the control group used conventional teaching methods. The findings show that the experimental group experienced significant improvement in critical thinking and problem-solving skills, as indicated by higher scores on the critical thinking and problem-solving tests compared to the control group. Additionally, observations during the learning process revealed that students were more active, more creative, and able to solve problems using more effective approaches. The study concludes that the PJBL model based on Tringo supported by VR technology can serve as an effective alternative for enhancing students’ critical thinking and problem-solving skills. The implementation of this model also shows high relevance in the context of future education, where digital skills and collaboration are essential.